Викладання в закладах вищої освіти - Євтушенко, В. Р. (ХНУРЕ, 2023)
Considering the problems of teaching in institutions of higher education, the question arises: how to make the learning process more accessible and effective for students? One of the solutions to this problem can be the use of modern neural networks, in particular Midjourney and ChatGPT. The use of neural networks in education is becoming more and more popular because they can improve the quality of teaching and learning. Neural networks such as Midjourney and ChatGPT can be useful tools to improve the quality of teaching and ensure effective learning by students. In this report, we will look at exactly how these neural networks can be applied in higher education and how they can help improve the quality of teaching.